Mechanical manipulations on electronic transport of graphene nanoribbons. (18th May 2015) - Wang, Jing; Zhang, Guiping; Ye, Fei; Wang, Xiaoqun
Abstract: We study the effects of uniaxial strains on the transport properties of graphene nanoribbons (GNRs) connected with two metallic leads in heterojunctions, using the transfer matrix method. Two typical GNRs with zigzag and armchair boundaries are considered and the tension is applied either parallel or perpendicular to the ribbon axis. It turns out that the electron–hole symmetry is missing in the gate voltage dependence of the conductance data of the armchair GNRs, while it persists in the zigzag ribbons under any strains. For an armchair GNR with a vertical tension applied, a sharp drop of conductance is found near the critical value of the strain inducing a quantum phase transition, which allows one to determine the critical strain accurately via measuring the conductance. In the zigzag ribbon, there exists a range of gate voltage around zero, where the conductance is insensitive to the small horizontal strains. The band structures and low-energy properties are calculated to elucidate the mechanism on the strain effects in GNRs. We expect that our results can be useful in developing graphene-based strain sensors.